Upcycling of brewers’ spent grains via solid-state fermentation for the production of protein hydrolysates with antioxidant and techno-functional properties - Chin, Yi Ling; Chai, Kong Fei; Chen, Wei Ning (Food Chemistry: X, 2022)
•Brewers’ spent grains (BSG) were fermented by a food-grade fungi.•Proteins and its hydrolysates were extracted using an ethanolic-alkali mixture.•Fermented BSG protein hydrolysates showed better functional properties.•The protein hydrolysates showed antioxidative and non-cytotoxic effects.•Application of the protein hydrolysates as a plant-based emulsifier was promising. Brewers’ spent grains (BSG) were fermented with Rhizopus oligosporus and up to 15% of original protein was hydrolysed. Fermented BSG was then subjected to an ethanolic-alkali extraction and isolated fractions contained 61–66% protein. An evaluation of functional properties suggested that fermented extracts presented superior emulsifying abilities (15–34 m2/g of activity and 16–42 min of stability), foaming properties (16–30% capacity and 7–14% stability), and water/oil binding capacities (0.41 g/g and 0.24 g/g, respectively). They also showed significantly higher ABTS inhibition and stronger reducing power than unfermented ones, indicating that fermented BSG protein extract had greater antioxidant activities. No cytotoxic effect was detected in the range of 2–10 mg/mL. When applied in a mayonnaise formulation, fermented hydrolysates demonstrated better emulsion stability in terms of creaming, microstructure and viscosity. Thus, fermented BSG protein is a potential plant-based emulsifier for food, pharmaceutical and cosmetic applications.